Modern Intellectual Slavery - Aghenitei, Mihaela; Chicos, Oana (Journal of Danubian Studies and Research, 2022)
Slavery from the medieval Latin sclavus - slavus refers to the human condition of persons (slaves) who work for a master without remuneration and who do not have rights over their own person. Slaves must obey all orders of the master from birth or capture (transition from freedom to slavery) to death or release (transition from slavery to freedom). From a historical point of view, slavery means, by definition, the denial of equality between people, and philosophically slaves were considered a separate and inferior species. This is also the condition of the expert before the court. The court may order at its discretion, without recourse to another expert in the field, the cutting of explanatory estimates regarding the costs involved in carrying out expertise’s in civil or criminal cases, the use of expert reports in cases after their annulment and taking the money back. The works of experts are most often accompanied copyright because many experts come from academic field, people who most often publish their work for teaching purposes. The profession of expert is a liberal profession, but through legislation and the attitude of magistrates, it has become a slavery, because most of the time the works of experts remain unpaid or at best, poorly paid far below their intrinsic value.